Lamotrigine Induced Hypersensitivity Syndrome in Pregnancy - Goel, P; Isher, H; Saha, Pradip Kumar; Tendon, R; Devi, L; Dhami, GP (Nepal Journal of Obstetrics and Gynaecology, 2013)
Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 68-70 DOI: http://dx.doi.org/10.3126/njog.v7i1.8843